Digestible Energy Intake and Digestive Efficiency of Human-Managed North American River Otters (Lontra canadensis). (20th January 2020) - Minter, Larry J.; Heugten, Kimberly Ange-van; Harms, Craig A.; Stoskopf, Michael K.
Abstract : Diets currently provided to captive North American river otters ( Lontra canadensis ) are highly variable with different institutions providing various whole foods, commercial complete prepared diets, or combinations of both. This study investigated the digestible energy intake, gastrointestinal transit time, and digestive efficiency of three different diets being fed at three North Carolina institutions. Otters housed at Institution A ( n = 3) were fed strictly fish. Otters housed at Institutions B ( n = 3) and C ( n = 2) were fed a majority fish based diet (58.5 and 74.1%, respectively), supplemented with fruits, vegetables, and supplemental protein sources as enrichment. There was an apparent trend between increased percentage of fish in the diet and faster transit time and higher digestive efficiency. As less fish was included in the diets, the GI transit time was longer (Institution A, 106 minutes; Institution B, 145 minutes; Institution C, 208 minutes). Median digestive efficiency was high for all three groups (A, 91.4%; B, 87.8%; C, 89.8%) but was higher for the institutions feeding fish. Additionally, the overall median gross energy intake for the eight animals in this study was 163.1 kcal/kgBM 0.75 /day (range: 92.2 to 260.7 kcal/kgBM 0.75 /day). While all three institutions had healthy otter populations, it appears that a higher fish diet should be further studied as the model North American river otter diet.